2015
DOI: 10.1080/10412905.2015.1043399
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation in phytochemicals of essential oil fromJuniperus communisneedles in western Himalaya

Abstract: Essential oil from Juniperus communis needles were examined in three different seasons (spring, rainy and winter) throughout the year for the analysis of yield and chemical composition. Volatiles of the needles were obtained by hydrodistillation process using clevenger type apparatus. The essential oil yield in all the seasons was not significantly changed and was found 0.29% (rainy), 0.3% (winter) and 0.33% (spring). Chemical compositions of the oils were analyzed by GC and GC-MS techniques on DB-5 capillary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 23 publications
3
10
1
Order By: Relevance
“…Earlier reported studies also detected sabinene as main oil component in J. communis (48.8 -61.09%). [38] [39] We have also observed high concentration of a-pinene and sabinene in J. recurva, which is in agreement with previous published report. [40] It has also been observed that a-pinene (49.0%) and d-3-carene (8.9%) were prevalent in wild J. communis compared to other Juniper species.…”
Section: Characterization Of Essential Oils Composition and Their Yieldsupporting
confidence: 93%
See 3 more Smart Citations
“…Earlier reported studies also detected sabinene as main oil component in J. communis (48.8 -61.09%). [38] [39] We have also observed high concentration of a-pinene and sabinene in J. recurva, which is in agreement with previous published report. [40] It has also been observed that a-pinene (49.0%) and d-3-carene (8.9%) were prevalent in wild J. communis compared to other Juniper species.…”
Section: Characterization Of Essential Oils Composition and Their Yieldsupporting
confidence: 93%
“…Earlier reported studies also detected sabinene as main oil component in J . communis (48.8 – 61.09%) . We have also observed high concentration of α ‐pinene and sabinene in J .…”
Section: Resultssupporting
confidence: 62%
See 2 more Smart Citations
“…Even more, in the study above it was found for the first time that needles and berries of the same plants produced essential oils of different chemotypes. Some needle essential oils of J. communis from Scandinavian countries, Poland, Iran, Portugal, France (Corsica Island), India and Italy (Sardinia Island) contained also predominant amounts of sabinene [23,28,30,31,[40][41][42][43][44][45].…”
Section: Cones Leavesmentioning
confidence: 99%